WET CHEMICAL SYNTHESIS, CHARACTERIZATION, AND ANTIBACTERIAL ACTIVITY OF MOLYBDENUM OXIDE NANOPARTICLES AGAINST STAPHYLOCOCCUS EPIDERMIDIS AND ENTEROBACTER AEROGENES - POONAM SANGWAN; HARISH KUMAR; RANI, RENU (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to synthesize the molybdenum oxide nanoparticles (NPs) by employing wet chemical method and investigation of their antibacterial properties against pathogenic bacteria. Methods: Molybdenum trioxide (MoO3) NPs were synthesized using an eco-friendly wet chemical sol–gel technique. The synthesized MoO3 NPs were characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier-transform infrared spectroscopy, and ultraviolet-visible spectroscopic techniques to confirm the obtained product, size shape, morphology, functional groups, and absorption spectra, respectively. The size of the MoO3 NPs was found to be 41 nm. The antibacterial activity of these metal NPs was investigated on Staphylococcus epidermidis and Enterobacter aerogenes by measuring the zone of inhibition and colony-forming units on solid medium and by measuring the optical density of the culture solution. Antibacterial activity of MoO3 NPs was also compared with well-known standard antibiotics. Results: The antibacterial activities of molybdenum oxide NPs possessing size 41 nm were compared with standard antibiotics such as oxacillin, cotrimoxazole, erythromycin, clindamycin, chloramphenicol, and tetracycline. It was found that all of these antibiotics were effective against Staphylococcus epidermidis while Enterobacter aerogenes was resistant to oxacillin, co-trimoxazole and clindamycin, whereas the MoO3 nanoparticles were found to be effective against both of these bacterial pathogens. Conclusion: Inorganic antimicrobial agents have advantages over organic antimicrobial agents due to their stability, preparation methods, and their ability to prevent bacteria to develop multidrug resistant. It was observed that MoO3 nanoparticles (NPs) possess good antibacterial properties; therefore, these can be used in pharmaceutical industries and provide a path for further research regarding the toxicity study for its use in human being.